Analysis of the translatome by ribosome profiling in colorectal cancer - Silva, Joana (2020)
Colorectal cancer (CRC) is a serious health problem due to its high incidence and mortality rates despite the major advances in cancer therapeutic approaches [1]. CRC carcinogenesis progression is based in a continuous accumulation of genetic alterations that leads to variations in the overall gene expression profiles [2]. This creates the need for deep analysis of cancer gene expression patterns and, thus, a more reliable understanding of the human proteome to disclose the molecular and cellular pathways as well as the regulatory mechanisms involved in cancer progression [2-4]. Genome wide analyses of gene expression have so far focused on the abundance of mRNA species as measured either by microarray or, more recently, by RNA deep sequencing [5,6]. However, neither approach provides information on protein synthesis, an important end point of gene expression [5,7]. Ribosome profiling is an emerging technique that uses deep sequencing to monitor in vivo translation and provide global and quantitative measurements of translation [7,8]. It can also reveal unexpected complexity in translation, including the presence of ribosomes outside of classical protein-coding regions of the transcriptome [5]. In this approach, translation is profiled by nuclease footprinting of ribosomes on RNA templates and high-throughput sequencing in order to determine the precise positions of ribosomes on a transcript and its overall density [8]. Ribosome profiling studies have been performed in cancer cell lines, where they showed an increase in overall protein identification and new proteins not yet annotated that possibly were originated from N-terminal extensions or upstream open reading frames (uORFs) [9-12]. The main goal of this project is to determine the changes between the translatome of CRC and normal colorectal cells and the role of such alterations in the tumorigenesis process of CRC cells. For this purpose, we will perform ribosome profiling in normal (NCM460) and CRC (HCT116) cell lines. Bioinformatics and gene ontology analysis of the translated mRNAs will elucidate the main cellular pathways through which the corresponding proteins are involved in CRC progression. Then, we will dissect which of these proteins can interfere and induce cell survival of CRC cells. Furthermore, we aim to analyze the potential contribution of translatable short alternative ORFs (AltORFs) and/or the corresponding peptides towards CRC progression. This information will be crucial to the development of new therapeutic strategies for CRC.